Supplemental Feeding Implementation: Window of Opportunities for the Intestinal Microbiota Development and Immune Responses Modulation - Irina A. Belyaeva; Leyla S. Namazova-Baranova; Elena P. Bombardirova; Regina A. Shukenbayeva; Tatyana V. Turti ("Paediatrician" Publishers LLC, 2023)
This review summarizes stages of intestinal microbiota development in infant and immune responses modulation associated to these stages. The leading role of breastfeeding in the optimal microbiota and associated immune responses development during the first half of child's life is presented. The biological feasibility of supplemental feeding implementation at the second window of opportunity (4-6 months) is justified, as well as role of supplementation products (including cereal) in adult microbiota development.